A Study of Seven Day Mortality in Acute Ischemic Stroke in a Teaching Hospital in Chitwan - Dewan, K R; Rana, P VS (Journal of Nepal Health Research Council, 2014)
Background: Stroke mortality rate indicates a measure in hospital quality care. Most of the available data are from developed countries and are for late mortality. Only few studies on 7-day fatality, a recently implemented indicator of early stoke mortality, are reported. We attempted to identify the predictors of clinical outcome by 7th day in acute ischemic stroke.Methods: This descriptive study included 100 consecutive cases of acute ischemic stroke admitted to Neurology center of a teaching hospital in Chitwan, Nepal. Common risk factors were identified. The cases were classified as per TOAST classification and severity at admission assessed using National Institutes of Health Stroke Scale. Univariate and multivariate analysis was used to analyze the data.Results: Thirteen percent patients expired by 7th day. On univariate analysis severity of stroke, fever, atrial fibrillation, hypertension at admission and early neurological deterioration were related to early 7-day mortality where as age, gender, smoking, diabetes mellitus, coronary artery disease, early onset seizures, dyslipidemaia, and hematocrit were unrelated to early mortality. Multivariate analysis showed that only NIHS score was significantly correlated with early mortality.Conclusions: A mortality rate of 13 percent was noted by 7th day. A positive association was noted with stroke severity, early neurological deterioration, arterial fibrillation, hypertension and fever at onset.Keywords: Early mortality; Early onset seizure; Early neurological deterioration; Ischemic stroke